2008
DOI: 10.1080/09737189.2008.11885250
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Life Satisfaction among Women

Abstract: Life satisfaction is widely considered to be central aspect of human welfare. Life satisfaction is not merely a judgment about one's life. For it is widely thought to involve affirming, endorsing, appreciating or being pleased with one's life. The present study is an attempt to evaluate life satisfaction among women and to analyze the influence of socio-personal characteristics of women with their life satisfaction. To fulfill these objectives, 120 women were selected from Jammu and Kashmir, through multi-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 8 publications
1
18
0
2
Order By: Relevance
“…Young age females were economically and personally unsatisfied as compared to higher age groups. This finding was supported by women from Jammu and Kashmir and United Arab Emirates [10][11][12][13][14]. Age is an important moderator of effect of marital status, income, health and social support upon LS.…”
Section: Discussionsupporting
confidence: 59%
“…Young age females were economically and personally unsatisfied as compared to higher age groups. This finding was supported by women from Jammu and Kashmir and United Arab Emirates [10][11][12][13][14]. Age is an important moderator of effect of marital status, income, health and social support upon LS.…”
Section: Discussionsupporting
confidence: 59%
“…For seniors and the elderly, financial and physical aspects are more significant in affecting life satisfaction. Age is also related to life satisfaction, as proven by Jan and Masood (2008). With age increment, life satisfaction was found to decrease by 40%.…”
Section: Introductionmentioning
confidence: 87%
“…For example, studies have found no significant differences in the life satisfaction scores for single, married, and divorced women (Jan and Masood, 2008). The factor for their life satisfaction is definitely varied as suggested by Kousha and Moheen (2004) who conducted a study among Iranian women living in urban areas.…”
Section: Populasi Volume 25 Nomor 1 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction with life may be different in terms of gender. However, few studies have investigated the particular predictors of life satisfaction for women (13), particularly in the Middle East region, and in countries with different social systems such as Iran. Thus, in the present study, QoL domains together with the individual items of the QoL and socio-demographic characteristics were used to explore whether they are determinants of life satisfaction, socio-demographic factors and all individual items of QoL.…”
Section: Introductionmentioning
confidence: 99%